A BIBLIOMETRIC ANALYSIS AND MAPPING STUDY OF RISK MANAGEMENT IN ISLAMIC FINANCIAL INSTITUTIONS - Alghamati, Adel K.; Azam, S. M. Ferdous; Khatibi, Ali (Bank Indonesia, 2024)
This paper performs a bibliometric analysis on risk management in Islamic financial institutions (IFIs), identifying significant research themes, influential authors, as well as emerging trends from 2003 to 2024. A systematic search strategy identifies 524 relevant publications from the Scopus and Web of Science databases. Using techniques from network analysis, science mapping, and performance analysis with the help of VOSviewer software, we find that 2020 and 2021, with 86 and 97 papers, are the most productive years in both databases. University of New Orleans and International Islamic University Malaysia are significant institutions. The most prominent journal is the International Journal of Islamic and Middle Eastern Finance & Management, which garners the highest number of citations. The Journal of Islamic Accounting and Business Research has the highest number of publications. Malaysia is a significant contributor to this field. Moreover, research on risk management in other sectors has been scant, concentrating solely on Islamic banking. Relying on particular databases and English-language publications could have eliminated relevant non-English research.